2013
DOI: 10.1002/masy.201200072
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion Copolymerization of Vegetable Oil Macromonomers Possessing both Acrylic and Allylic Functionalities

Abstract: Summary: A soybean oil-based vegetable oil macromonomer (VOMM) was incorporated as a comonomer into an all-acrylic copolymer via semi-continuous emulsion polymerization. Structurally, VOMMs are comprised of long hydrocarbon fatty acid moieties with allylic double bonds which enable auto-oxidative crosslinking at ambient temperature. VOMMs facilitate low temperature film formation and the fatty acid chains tethered to the polymer backbone auto-oxidize upon film formation to yield crosslinked films. Latexes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…The incorporation of plant oil-based monomers in copolymerization with conventional petroleum-based counterparts provides several benefits to the final copolymers such as plasticizing properties, the elimination of coalescence aids in latex applications, reducing minimum film formation temperature and film-forming properties. The ability of fatty acid fragments to undergo autoxidation (due to presence of allylic double bonds in resulting macromolecules) after latex application and yield the crosslinked polymer networks can balance the mechanical properties of final latex products, which can be beneficial as well 13,17,20 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incorporation of plant oil-based monomers in copolymerization with conventional petroleum-based counterparts provides several benefits to the final copolymers such as plasticizing properties, the elimination of coalescence aids in latex applications, reducing minimum film formation temperature and film-forming properties. The ability of fatty acid fragments to undergo autoxidation (due to presence of allylic double bonds in resulting macromolecules) after latex application and yield the crosslinked polymer networks can balance the mechanical properties of final latex products, which can be beneficial as well 13,17,20 .…”
Section: Introductionmentioning
confidence: 99%
“…The ability of fatty acid fragments to undergo autoxidation (due to presence of allylic double bonds in resulting macromolecules) after latex application and yield the cross-linked polymer networks can balance the mechanical properties of final latex products, which can be beneficial as well. 13,17,20 Another interesting plant-based renewable resource which has attracted a lot of attention in the past few years is cardanol. This is a byproduct from the cashew nut industry and refers to an aromatic class of organic compounds.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] In this regard, Kaya et al reported synthesis of latexes with varying amounts of soybean oilbased macromonomers in copolymerization with methyl methacrylate. 15 Moreno et al used miniemulsion polymerization to polymerize monomer synthesized by incorporation of methacrylic functionality into linoleic acid. 16 Fully renewable polymer latexes based on naturally occurring α-methylene-γ-butyrolactone were synthesized in miniemulsion in.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetable oil macromonomers (VOMMs) have distinct characteristics that are advantageous in the synthesis of environmentally responsible emulsions: (1) by virtue of its molecular length and large monomer size, the monomers are typically excellent plasticizers and readily facilitate coalescence without the necessity for solvent‐based coalescing agents, (2) the monomers readily copolymerize in emulsion polymerization with a variety of vinyl monomers through the acrylate functionality and reduce minimum filming temperature (MFT) during film formation while preserving the allylic functional group (at the polymerization stage), and (3) the allylic functionalities within the fatty acid residue, i.e., monomer tail, react auto‐oxidatively after application and slowly during coalescence at ambient temperature, resulting in crosslinked film networks that improve mechanical strength through upward shifted resulting T g s. The synergistic combination of allylic vegetable oil fatty acids and an acrylic backbone provides mechanically stable, self‐crosslinking emulsions with unique structure and design capabilities for utilization in reduced or zero VOC emission coatings …”
Section: Introductionmentioning
confidence: 99%